The Four Saleh Characters/Tabiat As The Foundation of Building A Value-Based Education - Widiantari, Dewa Ayu; Artaningsih, Luh (Jayapangus Press, 2023)
Value-based education is regulated in securing development that requires complete integration between body, mind and heart, as well as channeling life energy in learning activities that contribute to the growth of the child's personality both internally and externally. This ethos of usefulness through value-based education is actualized in social spaces as the maturation of all forms of strengthening human potential based on values. Value-based education as an instrument seeks to create awareness of the importance of values ​​in the process of transferring knowledge and involves consideration of the ethical consequences of fulfilling one's rights in social praxis which is integrated through the four Tabiat Saleh as guides in realizing everything related to efforts to maintain and develop knowledge. These four Tabiat Saleh form the basis of the main moral teachings in Pancasila, by maintaining the values ​​of human life, and religious values ​​in carrying out physical and spiritual actions in accordance with the unity of human nature as individual beings and social beings, all in a harmonious balance and dynamic.